Factors affecting the consumers’ embracement of manual self-ordering system (order chit) in restaurants - Chong, Daniel Ka Leong * (Routledge, 2021)
The upsurge of manpower crunch issues has tightened up the service capacity of many full-service restaurants. The introduction of manual self-ordering system (as opposed to electronic menu and computerized ordering system) was the outcome of the manpower shortage among many financially restricted small- to mid-scale restaurant operators in Malaysia. Past studies pertaining to self-service restaurants mainly focused on multinational fast-food chain’s counter service, e-menu, electronic ordering system, and online food ordering system. The purpose of this research is to identify factors affecting Malaysian consumers’ acceptance toward the use of order chit as a form of self-ordering system within the casual dining establishments. Specifically, the study focused on the context of mid-scale casual dining restaurants. Based on the literature review, a hypothetical construct of factors determining the adoption of order chit system was proposed. The model was then tested using data collected from a sample of casual dining restaurant patrons residing in the Klang Valley of Malaysia. Results of a structural equation analysis suggest that ease of use, information clarity, perceived service, and ordering technique fit, and freedom of choice are found to be significant in increasing the acceptance of order chit system. However, peer pressure was found to not significantly affect the acceptance of such practices. The academic and managerial implications of these findings are considered.